Internet of things, smart spaces, and next generation networks and systems : 17th International Conference, NEW2AN 2017, 10th Conference, ruSMART 2017, Third Workshop NsCC 2017, St. Petersburg, Russia, August 28-30, 2017, Proceedings /: 17th International Conference, NEW2AN 2017, 10th Conference, ruSMART 2017, Third Workshop NsCC 2017, St. Petersburg, Russia, August 28-30, 2017, Proceedings. (2017) - Unknown
No abstract available